THU0382 Change in sacroiliac joint structural radiographic damage after two years of etanercept therapy in comparison to a contemporary control cohort in non-radiographic axial spondyloarthritis. (15th June 2017) - Dougados, M; Maksymowych, WP; Landewe, R; Molto, A; Claudepierre, P; Hooge, M de; Lambert, RG; Bonin, R; Bukowski, JF; Jones, H; Logeart, I; Pedersen, R; et al.
Abstract : Background: Despite the well-known symptomatic and anti-inflammatory effect of TNF inhibitors in axial SpA (axSpA), demonstrating a structural effect is challenging. Objectives: To compare 2 yrs of radiographic sacroiliac joint (SIJ) changes in pts receiving etanercept (ETN) in a clinical trial to similar pts not receiving biologics in a cohort study. Methods: Pts had recent onset non-radiographic (nr)-axSpA fulfilling ASAS criteria. Study group: pts receiving ETN 50 mg once weekly for 2 yrs in EMBARK (NCT01258738 ). Control group: pts in an ongoing longitudinal cohort study not receiving biologics for 2 yrs (DESIR, NCT01648907 ). Outcome measure: change in x-ray SIJ score per mNY criteria (0–4 per SIJ). X-rays were read by 3 experienced readers unaware of image chronology and pt group. Primary endpoint: change (mean of 3 readers) in total SIJ score (-8 to +8). Binary endpoints: (1) shift from baseline (BL) mNY+ to wk-104 mNY- and vice versa; (2) change in SIJ score ≥1 (left or right SIJ); (3) change in SIJ score ≥1 in ≥1 SIJ, with change from 0 to 1 and from 1 to 0 considered no change. Treatment effect was analyzed without and with adjustment for the baseline (BL) covariates of sex, symptom duration, smoking status, HLA-B27 status, ASDAS-CRP, SPARCC MRI SIJ score, and SIJ radiography score. Results: At BL, the control (DESIR, N=197) and ETN (EMBARK, N=164) cohorts differed significantly in all covariates listed above. The difference in change in total SIJ score for control vs ETN, adjusted for covariates, was small but significant: least-squares mean (95% CI): 0.08 (-0.03, 0.20) vs -0.14 (-0.26, -0.01); p =0.008. The table presents x-ray changes. When adjusted for covariates, the mean difference between control and ETN was significant for 2 of the 3 binary endpoints (table). Conclusions: This analysis confirms the slow rate of radiographic SIJ progression over 2 yrs in nr-axSpA. The observed data suggest a lower rate of progression with ETN than without a TNF inhibitor. Disclosure of Interest: M. Dougados Grant/research support from: Pfizer, Abbvie, UCB, Merck, Lilly, Sanofi, Consultant for: Pfizer, Abbvie, UCB, Merck, Lilly, Sanofi, W. P. Maksymowych Grant/research support from: AbbVie, Pfizer, Sanofi, Consultant for: AbbVie, Amgen, Eli Lilly, Janssen Pharmaceutica, L.P, Novartis, Pfizer, Sanofi, UCB, R. Landewe Grant/research support from: Abbott, Amgen, Centocor, Novartis, Pfizer, Roche, Schering-Plough, UCB, Wyeth, Consultant for: Abbott/Abbvie, Ablynx, Amgen, Astra-Zeneca, BMS, Celgene, Janssen (formerly Centocor), Galapagos, GSK, Novartis, Novo-Nordisk, Merck, Pfizer, Roche, Schering-plough, TiGenix, UCB, Wyeth, Employee of: Is a director of Rheumatology Consultancy BV, A. Molto Grant/research support from: Pfizer, UCB, Consultant for: Abbvie, BMS, MSD France- Merck, Pfizer, UCB, P. Claudepierre Grant/research support from: Pfizer, Roche-Chugai, MSD, Consultant for: Abbvie, BMS, Celgene, Janssen, Novartis, Merck, Pfizer, Roche, UCB, M. de Hooge: None declared, R. G. Lambert Consultant for: Bioclinica, R. Bonin Shareholder of: Pfizer, Employee of: Pfizer, J. Bukowski Shareholder of: Pfizer, Employee of: Pfizer, H. Jones Shareholder of: Pfizer, Employee of: Pfizer, I. Logeart Shareholder of: Pfizer, Employee of: Pfizer, R. Pedersen Shareholder of: Pfizer, Employee of: Pfizer, A. Szumski Employee of: InVentiv Health, B. Vlahos Shareholder of: Pfizer, Employee of: Pfizer, D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boeringer Ingelheim, Celgene, Daiichi, Eli-Lilly, Galapagos, Gilead, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, UCB, Employee of: Director of Imaging Rheumatology bv.